The impact of economic complexity and exchange rate on current account balance : a comparative analysis of SADC and ECOWAS as countries - Mogashwa, Phillip Tumelo (My University, 2023)
The study compares the impact of economic complexity and exchange rates on current account balances in the SADC and ECOWAS regions from 1997 to 2018. Due to data availability constraints, only five SADC countries and four ECOWAS member states represent the relevant regions. The study used the panel Autoregressive Distributed Lag (ARDL) technique, Granger causality, variance decomposition, and impulse response tests. Two variables, foreign direct investment and exports of goods and services were included as control variables in the models of the study. The empirical evidence revealed similar long-run results for both economic regions in terms of the impact of economic complexity, exchange rate, and foreign direct investment. The findings also revealed that both economic complexity and foreign direct investment have a negative impact on the current account, whereas the exchange rate has a positive relationship with the current account balance. Most notably, the exposition of the positive impact of the exchange rate, in the long run, is consistent with the long run proposition of the J-curve theory but was found to be contrary in the short run. Exports of goods and services, on the other hand, have been shown to have a negative impact on the SADC region's current account balance while having a positive impact on the ECOWAS region. The short run estimates show contradictory results across regions. Granger causality test results revealed three one-sided causalities for the SADC grouping and two bidirectional causalities between exports and exchange rates and exports and foreign direct investment. Correspondingly, Granger causality tests for ECOWAS revealed bi-directional causality between exports and foreign direct investment. The generalised impulse response function results for each region are consistent with long run estimates, while variance decomposition revealed that the shocks from current account own innovations account for considerable fluctuations in both SADC and ECOWAS. The study recommends that the complexity of the local economy's structures and the productive capacity of the regions be improved to reap benefits from the products they export.
Thesis ((M.Com. ( Economics)) -- University of Limpopo, 2023
Keywords: Exchange rate; Economic complexity; Current account balance; SADC; ECOWAS; Foreign exchange rates; Balance of payments